A mysterious myopic surprise. Issue 2 (February 2022) - Fram, Nicole R.; Bedrood, Sahar; Durr, Georges M.; Liaboe, Chase A.; Samuelson, Thomas W.; Shah, Manjool; McCabe, Cathleen
Abstract : A diagnostic challenge of managing a myopic surprise with slightly elevated IOP after uneventful cataract surgery in a patient with a history of chronic angle-closure glaucoma. Abstract : A 73-year-old man with an ocular history of inactive age-related macular degeneration and chronic angle-closure glaucoma (CACG) in both eyes recently underwent femtosecond laser–assisted cataract surgery/phacoemulsification and intraocular lens (IOL) implantation with simultaneous Hydrus microstent (Ivantis, Inc.) implantation in the left eye. Although there was some reported subincisional iris prolapse due to intraoperative floppy iris, the case was otherwise uneventful according to the referring surgeon. Two months postoperatively, he was referred to our office for a myopic surprise of approximately 2.0 diopters (D) in the left eye (Figure 1 ). Of note, he has a distant history of acute ACG and complicated cataract surgery in the right eye with a failed trabeculectomy. He subsequently had laser peripheral iridoplasty to pull the iris away from the angle in the right eye (Figure 2 ). His topical intraocular pressure (IOP)-lowering medications at presentation included dorzolamide-timolol 1 drop twice daily in the left eye and 1 drop of timolol in the right eye once daily. His past medical history is significant for hypertension and benign prostatic hyperplasia, and his oral medications include Tamsulosin (Flomax), Irbasartan (Avapro), and Atenolol. On examination, he had an UCDVA of 20/20 in the right eye and 20/80 in the left eye, and a BCDVA of 20/20 in the right eye and 20/25 in the left eye. His manifest refraction was plano in the right eye and 1.50 −0.75 × 90 in the left eye. IOP measured 19 mm Hg in the right eye and 26 mm Hg in the left eye. Pupil examination revealed a nonreactive pupil in the right eye and a round sluggish pupil in the left eye without an obvious relative afferent pupillary defect. Extraocular motility and confrontational visual fields were full in both eyes. On slitlamp examination, pertinent findings included the following: 1+ corneal guttata without edema in both eyes; anterior chambers were shallow but adequate in both eyes with scattered peripheral anterior synechiae in the right eye and a uniformly shallow but adequate chamber in the left eye; there was no cell or flare in either eye. Iris findings included a surgical pupil with a fibrotic pupillary membrane, laser iridoplasty scars with scattered temporal transillumination defects (TIDs) in the right eye, and 2.5 clock hours of TIDs and a patent peripheral iridotomy at 1 o'clock in the left eye; lens examination revealed centered posterior chamber IOLs with open posterior capsules in both eyes and lens pitting in the left eye. Pertinent findings on dilated fundus examination included a cup-to-disc ratio of 0.3 in both eyes with good neuroretinal rims and macular examination revealed medium-sized drusen with pigment clumping in both eyes and no active choroidal neovascular membranes. The remainder of the examination was unremarkable. What is the etiology of this myopic surprise? What diagnostic testing will help confirm the diagnosis and what are the best management options for this patient?